Enterovirus infections in England and Wales, 2000–2011: the impact of increased molecular diagnostics. (11th August 2014) - Kadambari, S.; Bukasa, A.; Okike, I. O.; Pebody, R.; Brown, D.; Gallimore, C.; Xerry, J.; Sharland, M.; Ladhani, S. N.; Zupanc, T. A.
Abstract There have recently been significant changes in diagnostic practices for detecting enterovirus (EV) infections across England and Wales. Reports of laboratory‐confirmed EV infections submitted by National Health Service (NHS) hospital laboratories to Public Health England (PHE) over a 12‐year period (2000–2011) were analysed. Additionally, the PHE Virus Reference Department (VRD) electronic database containing molecular typing data from 2004 onwards was interrogated. Of the 13 901 reports, there was a decline from a peak of 2254 in 2001 to 589 in 2006, and then an increase year‐on‐year to 1634 in 2011. This increase coincided with increasing PCR‐based laboratory diagnosis, which accounted for 36% of reported cases in 2000 and 92% in 2011. The estimated annual incidence in 2011 was 3.9/100 000 overall and 238/100 000 in those aged <3 months, who accounted for almost one‐quarter of reported cases (n = 2993, 23%). During 2004–2011, 2770 strains were submitted for molecular typing to the VRD, who found no evidence for a predominance of any particular strain. Thus, the recent increase in reported cases closely reflects the increase in PCR testing by NHS hospitals, but is associated with a lower proportion of samples being submitted for molecular typing. The high EV rate in young infants merits further investigation to inform evidence‐based management guidance.